Antibacterial Activity of Kersen Leaf Extract (Muntingia calabura Linn.) Against Salmonella typhi and Staphylococcus aureus Using Bioautography Method - Maharani, Dhea Nur Fadillah; Almeida, Maria; Arifian, Hanggara; Ibrahim, Arsyik; Herman, Herman (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2025)
Kersen (Muntingia calabura Linn.) is a plant with a large population in Indonesia. Thus, the abundance of this number can be used as a source of raw materials for medicine. Kersen has many benefits, especially in the leaves as an antibacterial. The purpose of this study was to determine the extract yield, compound groups, and antibacterial activity against Salmonella typhi and Staphylococcus aureus. Antibacterial activity was measured using the well method and TLC Bioautography. The results showed an extract yield of 19.77%. The TLC profile identified flavonoid, alkaloid, tannin, and steroid compound groups. Kersen leaf extract showed antibacterial activity against Salmonella typhi and Staphylococcus aureus with moderate to strong antibacterial power at concentrations of 40%, 50%, and 60%. The groups of compounds suspected of playing a role in antibacterial activity are flavonoids, alkaloids, tannins, and steroids. This study shows that kersen leaf extract has the potential as an antibacterial agent against Salmonella typhi and Staphylococcus aureus bacteria.